Response to fertilization and planting density in maize lines. - Tosquy, Hugo (2016)
An experiment was carried out in the Cotaxtla Experimental Field during the 1995 spring-summer cycle to study effects of soil mineral fertilization and population density in six parentallines of the best hybrids from tropical Mexico. The experimental desigp. used was the randomized block s in divided plots with two repetitions, and a complete factorial treatment design 24. Large plots consisted of lines LE-36, LE-37, LRB-14, D-539, POB 21 and POB 43. Small plots were formed by the treatments resulting from the combination of plant density (PD) at 50, and 62.5 thousand pl/ha, nitrogen (N), phosphorus (P) and potassium (K) at 161-184,46-69 and 0-60 kilograms per hectare, respectively. Out of the 18 variables studied, only 4 were not significant for the lines. The density of 62,500 pVha showed the highest grain yield. However, the same trait did not respond to a more intense fertilization with N-P-K, but the combination of each major primary element at its highest level helped to stop the negative effect of high density in grain traits. There was an additive effect in the interaction lines x density for grain yieId. This variable increased in all lines when there was a greater number of pIants per area unit.